Perlindungan Hukum terhadap Konsumen dalam Kontrak Bisnis Properti - Rikky Nelson Manurung; I Made Kantikha (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Property business is the activity of buying and selling a plot of land or house involving 2 (two) parties between the seller (business actor) and the buyer (consumer), in its implementation gives birth to legal relationships carried out through agreements. Quality in running a property business, business actors selling their plot of land to consumers are inseparable from the fact that the business actor gets the land previously from the landowner to then sell it to consumers. The method used in this study is Normative Juridical. The legal protection of agreements made by business actors and consumers in the property business is guided by articles 1320 and 1338 of the Civil Code. Breach of promise not to carry out the agreed is a form of default committed by one of the parties to the agreement as regulated by article 1234 of the Civil Code which can be resolved with a "win and win solution" through negotiations so that business actors and consumers are protected. Consumer protection in property business agreements starts from the beginning of the purchase, making the agreement, payment to the sale and purchase deed agreement. Consumers who have signed the agreement means that they have agreed to all the terms and conditions that have been set. All of these agreements, both oral, written, and deed are not authentic. Authentic deeds that are carried out legally, as long as consumers have fulfilled their achievements by making payments in full, not negligently, in accordance with their rights and obligations in Law no. 8 of 1999, consumers are obliged to get legal protection.